HIV and kidney diseases: 35 years of history and consequences. - Campos, P (2016)
Kidney diseases in human immunodeficiency virus (HIV)-infected patients are often misdiagnosed. Despite reductions in morbidity and mortality owing to widespread use of highly effective combination antiretroviral therapy (cART), acute kidney injury (AKI) and chronic kidney disease (CKD) are still more common in these patients than in the general population, and are associated with poor health outcomes. HIV-associated nephropathy and HIV immune complex kidney diseases are the more recognizable HIV-related kidney diseases. However, a broad spectrum of kidney disorders related or not directly related with HIV infection can be observed, including cART-induced AKI, CKD, proximal tubular dysfunction, crystalluria and urolithiasis, among others. This review summarizes the major epidemiologic studies of kidney diseases in HIV-infected patients, discusses novel approaches that may potentially limit nephrotoxicity such as the use of tenofovir alafenamide, and outlines current screening measures for early diagnosis of kidney dysfunction or tubular damage, and for accurate detection of increased risk for acute or chronic kidney diseases.